Non-heart beating organ donation: overview and future perspectives. - Moers, C; Leuvenink, H; Ploeg, R (2007)
New indications for organ transplantation combined with a stagnating number of available donor grafts have severely lengthened the waiting list for almost all types of transplantations. This has led to a renewed interest in non-heart beating (NHB) donation, as a possible solution to bridge the gap between supply and demand. In this review, we present an overview of current NHB donation practice, outcome, existing problems and future perspectives. We focus on possible improvements in donor management, recipient care and new methods of organ preservation that may be better suited for these marginal organs. Successful institution of NHB protocols depends on adapting current transplantation practice at all levels, which is one of the greatest challenges for researchers and professionals in this interesting re-emerging field.